Nelayan Danau Tempe: Strategi Adaptasi Masyarakat dalam Menghadapi Kondisi Perubahan Musim - Icha Musywirah Hamka; Hamka Naping (ETNOSIA : Jurnal Etnografi Indonesia, 2019)
This article aims to describe how the economic culture of fishing communities in the area of Lake Tempe, Wajo Regency, South Sulawesi, in the face of tough times in two seasons. The existence of Lake Tempe made a lot of people who lived around him rely and making the Lake as a place to look for earnings. Its unique characteristics make Lake Tempe utilized in different ways in accordance with the seasons. It makes the community experience different issues between rainy season and dry season. This research used qualitative methods to get the depiction as a whole on the question of research. The results showed that the activity of fishing communities is changing depending on the season. It has resulted in the community get to know two of the famine, with different problems. The difference of the season brings socio-economic conditions of the difference is then also bring the community on different adaptation patterns. In the rainy season, people are faced with the problem of floods, and in the dry season, people should experience times of economic hardship. For that matter, any other uses different patterns. The rainy season, they adapt by designing the House in accordance with the conditions of the flood. They made rakkeang, bale-bale, Pallangga and patto'do. In the dry season, they overcame economic hardship by switching professions to become farmers, builders, and other informal sector jobs.